Vozes de professores: indícios de/para cursos de formação - Cavalcanti, Jauranice Rodrigues; Mendonça, Marina Célia [UNESP]; Branquinho, LÍlian; Cardoso, Rosana (Universidade Estadual de Londrina, 2011)
In this article we analyze discourses of teachers on the linguistic practices of their students and discourses of future teachers. We consider studies of Bakhtin on dialogism and ideology in the production of meanings. Results indicate the following conclusions: the student in the analyzed discourses is a bad speaker, a bad writer, a bad reader, the great villain of language and reading in school is the advent of new technologies and languages which introduce new practices that have not been accepted by the interviewees. In this discourses, we can notice ways that can be taken into consideration in new teacher’s formation courses.

Neste artigo, analisamos discursos de professores sobre as práticas linguísticas de seus alunos e discursos de futuros professores. Partimos de estudos de Bakhtin sobre as vozes sociais em confronto e os valores ideológicos na produção de sentido. Resultados apontam para as seguintes conclusões: o aluno, nos discursos analisados, é mau falante, mau escritor, mau leitor; o grande vilão da linguagem e da leitura, na escola, é o advento de novas tecnologias e linguagens, que introduzem novas práticas ainda não aceitas pelos entrevistados. Nesses discursos, vislumbram-se caminhos a serem percorridos em novos cursos para formação de professores.
Teacher’s voices: signs by/for formation courses
Keywords: Reading; Writing; Teaching; Discurso científico; Discurso do senso comum; Discurso sobre língua; Estudos bakhtinianos